Development of advanced practice competency standards for dietetics in Australia. Issue 4 (21st June 2017) - Palermo, Claire; Capra, Sandra; Beck, Eleanor J; Dart, Janeane; Conway, Jane; Ash, Susan
Abstract : Aim: This study aimed to explore the work roles, major tasks and core activities of advanced practice dietitians in Australia to define the Competency Standards for advanced practice. Methods: A qualitative approach was used to review advanced dietetic practice in Australia involving experienced professionals, mostly dietitians. Four focus groups were conducted with a total of 17 participants and an average of 20 years experience: 15 dietitian practitioners plus 2 employers (1 dietitian and 1 non‐dietitian). The focus groups explored the key purpose, roles and outcomes of these practitioners. Data from the focus groups were confirmed with in‐depth interviews about their core activities with a purposive sample of 10 individuals recently recognised as Advanced Accredited Practising Dietitians. Data from both focus groups and interviews were analysed adductively to identify key themes. Results: The key theme that emerged to define advanced dietetics practice was leadership, with four subthemes that described in more detail the major work roles and outcomes of advanced practice. These subthemes identified that advanced practitioners were (i) outcome‐focused, having impact; (ii) influence others and advocate; (iii) innovate and embrace change; and (iv) inspire others and are recognised for their practice. These outcomes were conceptualised within a broad generalist framework to generate revised Competency Standards. Conclusions: This study confirmed that leadership rather than specialist practice skills is the key determinant of advanced practice.